Customer Satisfaction of logistics Companies in Indonesia - Athiyyah Nasywa Kirana; Zahra Fatikhah Al Kahfi; Dinar Dewi Kania; Agus Setiawan (Green Publisher, 2025)
Indonesia's logistics business is expanding rapidly due to economic expansion, e-commerce, and worldwide trade. The country's diversified topography, cultural heritage, and insufficient infrastructure make it a difficult destination for multinational logistics businesses like FedEx and DHL. These businesses play a significant role in facilitating trade by offering reliable transportation and delivery services. This thesis examines their competition in the Indonesian market, providing ideas for improving operational performance and customer happiness. According to the report, both organizations face unique problems and possibilities in the Indonesian market, with key aspects such as delivery speed, reliability, price, and customer service playing a significant role in their competitiveness.Using a quantitative approach, the study aimed to measure and compare the performance of FedEx and DHL in the field of primary logistics services in Indonesia. It identified and measured the key factors that influence customer satisfaction and statistically compared customer satisfaction scores between the two. Based on the analysis results, both FedEx and DHL showed good performance in customer satisfaction, but there were notable differences: FedEx had an R-Square Customer Satisfaction of 0.758, indicating that 75.8% of the variation in customer satisfaction could be explained by factors like Cost Efficiency and Delivery Time. DHL, on the other hand, had a higher R-Square Customer Satisfaction of 0.828, showing that 82.8% of the variation could be explained by similar factors. This suggests that DHL is superior in terms of customer satisfaction, with a higher ability to explain the variation in satisfaction levels. While both companies performed well, DHL holds a greater advantage in maximizing customer satisfaction. The study concludes with recommendations for FedEx and DHL to improve their operational strategies and service quality in Indonesia, resulting in higher customer satisfaction and a competitive edge in the quickly evolving logistics business.